A Comparison of the Present and Proposed OR Department of Cardinal Santos Medical Center, Using Evidence-Based Design Criteria - Dalmacio, Ronald John B. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 9, 2023)
Designing Surgery Departments in the Philippine setting is a challenge for architects. The lack of information on how to validate design elements can lead to calculable consequences determined by the hospital’s turnover time and profit. Often, any architect who will explore a way to design these departments would initiate a trial-and-error design process because of the lack of knowledge and information to the needs of both the patients and the staffing—nurses, doctors, office staff, etc. This design problem is called Design Dilemma by Lauren Thomas (2010). Design Dilemma is experienced whenever a design problem, such as how to design an Operating Department, leads into a paralysis from the analysis due to the complexity of the users involved, as well as the lack of formal experimentation into the relationship between facility design and its effects on the operations. Ultimately, it results to a design qualified by the number of surgery cases served per day. Krupka, & Sandberg (2006) stated that operating room management focuses on reducing wasted time to perform more cases in regular business hours, reduce overtime, or provide a better experience for staff and patients. All of this will be contextualized into Philippine medical facilities which hospital architects in the country need as a guide to newer hospitals in the future.